PENGUKURAN KINERJA PERGURUAN TINGGI DENGAN PENDEKATAN BALANCED SCORECARD - Azura Luthfiyah Ara; Muhammad Ahyaruddin; Siti Samsiah (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2023)
This study aims to examine the influence of customer perspective, internal business process perspective, financial perspective and learning and growth perspective on Higher Education performance measurement. The research method used in this study is quantitative. The population in this study is Pekanbaru City College which amounts to 30. The type of data used is primary data obtained from questionnaires. The sample selection technique uses saturated sampling, so that the number of respondents in this study is 90 to 30 universities in Pekanbaru. The data analysis technique uses multiple linear regression analysis equations in the SPSS program. The results of this study show that the customer perspective, the internal business process perspective and the learning and growth perspective is not influence on the measurement of college performance. The financial perspective influence the measurement of higher education performance.